2014
DOI: 10.1007/s00264-014-2581-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the medial meniscus in different conditions on anterior tibial translation in the anterior cruciate deficient knee

Abstract: Additional injury of the medial meniscus increased aTT as well as aTT under a combined rotatory load in the ACL-deficient knee whereas repair of the meniscus significantly decreased aTT. Therefore, the meniscus status does have a significant impact on knee kinematics in the ACL-deficient knee. The present biomechanical study further highlights the importance of preserving the meniscus especially in patients with additional ACL injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 43 publications
1
61
1
1
Order By: Relevance
“…Therefore, it is expected that laxity's changes are easier to detect in an in vivo set-up. Lorbach et al [11], testing cadaveric specimens, found that partial or total meniscectomy of the medial meniscus determine a significant impact on knee kinematics in the ACL-deficient knee evaluated by Lachman and pivot-shift test, whereas the repair of the meniscus was able to reduce it, similar to the ACL-deficient knee with intact meniscus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is expected that laxity's changes are easier to detect in an in vivo set-up. Lorbach et al [11], testing cadaveric specimens, found that partial or total meniscectomy of the medial meniscus determine a significant impact on knee kinematics in the ACL-deficient knee evaluated by Lachman and pivot-shift test, whereas the repair of the meniscus was able to reduce it, similar to the ACL-deficient knee with intact meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Lorbach et al [11,Abstract Purpose The purpose of the present study was to determine, in vivo, the effect of different types of meniscectomy on an ACL-deficient knee. Methods Using a computer-assisted navigation system, 56 consecutive patients (45 men and 11 women) were subjected to a biomechanical testing with Lachman test (AP30), drawer test (AP90), internal/external rotation test, varus/valgus rotation test and pivot-shift test.…”
Section: Introductionmentioning
confidence: 99%
“…A single radial cut is equivalent to meniscectomy as it cuts off the hoof stresses across the circumferential fibers of the meniscus. Medial meniscectomy has been found to increase anterior tibial translation in ACL deficient knees by Lorbach et al [4] Total lateral meniscectomy is also associated with increase posterolateral rotary instability postoperatively due to its anatomical proximity to popliteus tendon and postero lateral capsule. Laprade et al has shown the importance of lateral meniscus in ACL reconstructed knees.…”
Section: Resultsmentioning
confidence: 99%
“…They also contribute mechanical stability of the knee along with cruciate ligaments specially rotary stability giving additional gliding function to the hinge type of knee joint [9] . Meniscectomy has bad influence on joint alignment, load distribution and anterior instablilty [3,4,5] . Medial meniscectomy increases tibio femoral contact stresses by 100% whereas lateral meniscectomy increases contact stresses by 200% to 300%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation